Biological Activities of Essential Oils Hydrodistillated from Two Closely Related Ginger Species: Alpinia malaccensis var. nobilis and Alpinia latilabris leaves - Jaya Vejayan, Palliah; Selladuri, Nathaniel Enock; Halijah, Ibrahim; Adawiyah Suriza, Shuib; M. M., Yusoff (Taylor & Francis, 2017)
The essential oils of A. malaccensis var. nobilis and A. latilabris were initially screened for antimicrobial activity against eleven microbes using the qualitative BacTiter GloTM kit followed by IC50 determination using the quantitative protocol of the same kit. The antioxidant activities were determined using DPPH radical scavenging test, ABTS and FRAP analysis. A. malaccensis var. nobilis showed inhibition of growth of 10 out of 11 microbes tested, with the most significant result observed for C. tropicalis and C. neoformans having IC50 of 1.75 mg/mL and 1.97 mg/mL, respectively. A. latilabris inhibited the growth of 8 out of 11 microbes, with the highest inhibition against K. pneumonia, having IC50 of 18.83 mg/mL. A. malaccensis var. nobilis also had a better antioxidant activity compared to A. latilabris. The IC50 for A. malaccensis var. nobilis was 32.67 mg/mL while 54.33 mg/mL for A. latilabris, using DPPH free radical scavenging assay. Measurements by ABTS and FRAP assays provided GAE value of 26.59 mg GAE/g and TE value of 24.56 M TE/g, respectively for essential oil of A. malaccensis var. nobilis while for A.latilabris, 14.47 mg GAE/g and 17.51M TE/g, respectively. GC analysis of the essential oil showed high presence of methyl cinnamate (60.26 %) and thymol (16.04%) in essential oil of A. malaccensis var. nobilis and phytol (91.75%) in essential oil of A. latilabris. In conclusion, A. malaccensis var. nobilis established to have generally better antimicrobial and antioxidant activities to its closely related species, A. latilabris.